2006
DOI: 10.2519/jospt.2006.36.2.45
|View full text |Cite
|
Sign up to set email alerts
|

An Electromyographic Analysis of Commercial and Common Abdominal Exercises: Implications for Rehabilitation and Training

Abstract: Study Design: A repeated-measures, counterbalanced design. Objectives: To test the effectiveness of 7 commercial abdominal machines (Ab Slide, Ab Twister, Ab Rocker, Ab Roller, Ab Doer, Torso Track, SAM) and 2 common abdominal exercises (crunch, bent-knee sit-up) on activating abdominal and extraneous (nonabdominal) musculature. Background: Numerous abdominal machine exercises are believed to be effective in activating abdominal musculature and minimizing low back stress, but there are minimal data to substant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
85
2
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(101 citation statements)
references
References 20 publications
7
85
2
7
Order By: Relevance
“…However, recent studies 17,20,[23][24][25] examining the muscle activity of the upper and lower rectus abdominal muscles during these motor tasks have reported that there is no difference between the muscle activity of the upper and lower RA and our results support these findings. Clark 17) suggested that the anatomical discovery that some RA fibers extend beyond the tendinous inscription might explain why there was no difference between upper and lower RA activity in the CU and DLL exercise tasks.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, recent studies 17,20,[23][24][25] examining the muscle activity of the upper and lower rectus abdominal muscles during these motor tasks have reported that there is no difference between the muscle activity of the upper and lower RA and our results support these findings. Clark 17) suggested that the anatomical discovery that some RA fibers extend beyond the tendinous inscription might explain why there was no difference between upper and lower RA activity in the CU and DLL exercise tasks.…”
Section: Discussionsupporting
confidence: 83%
“…This disagreement may result from differences in the maneuvering and displacement of the recording electrodes used in each study. The %MVC of the upper and lower RA obtained during Normal in the CU test corresponded with results from previous studies that examined this task as a rehabilitation training 24,25) . Although we could not fully compare the DLL test, our data during Normal were similar to the data of Lehman and McGill 24) .…”
Section: Discussionsupporting
confidence: 72%
“…Although muscle activities in each muscle grade in the CU test were signifi cantly larger than those in the DLL test, there was no difference between the two tests in the state (i.e., activity ratio) of the muscle activity. Recent studies have reported that there was no difference between the muscle activities of the URA and the LRA 2,3,23,29) , and the present study also failed to fi nd any difference in URA and LRA activity ratios between the tests performed by young subjects. Clark et al could not explain any difference in muscle activity between the RA muscle sites due to several RA fibers extending beyond the tendinous inscription 23) .…”
Section: Discussioncontrasting
confidence: 38%
“…g . r e c t u s a b d o m i n a l m u s c l e , R A ) , i s recommended for the prevention and treatment of LBP 2,3) .…”
Section: Introductionmentioning
confidence: 99%
“…It has to be noted that tactile suppression on the chest was quite high during back movements. A possible explanation for this observation is that the back movements, by the active contraction of muscles in the abdomen, may also have activated the chest muscles (Escamilla et al, 2006).…”
Section: Discussionmentioning
confidence: 99%